Production scheduling practice - Liew,, Kiat Juang. (UNIMAS, 2006)
Today’s businesses are competing increasingly on time and quality. To remain competitive, proper production scheduling system is very necessary.Production scheduling is the activities performed in manufacturing companies to manage and control the execution of the production process. Resources are known as part of important component in production scheduling and it should be utilize wisely to meet organization’s goal.Type of scheduling approach used may vary according to the production environment, management of the company and organization. The objective of this project is first to identify and investigate the factors that contribute to the problems/difficulties during production scheduling in the company under studied.Then the effects of poor production scheduling are studied. Next, type of scheduling technique used by the company under studied would be identified and recommendations are provided to solve the problems regarding production scheduling. The selected factory for the case study is ceramic tile manufacturer and distributor.Self observation and interviews are conducted to collect all the required data and information. The data and information are studied for the problems met during production scheduling and its effects then the suitable recommendations are suggested. From the results, the company is using Enterprise Resource Planning (ERP) System as the scheduling tool. ERP system itself is link to the sales department, scheduler, production personnel, work center manager, inventory section, and purchasing department. During the scheduling process, the company has met a lot of problems. The major problems faced are raw material problem, machine unavailability, raw material shortage, inaccurate information and poor performance feedback.It can be concluded that these problems have direct impact on production v and scheduling process. At the end of chapter, recommendations for each problem are provided.